Mind Mapping as an Instructional Strategy for Enhancing EFL Students’ Reading Comprehension in Vocational School in West Nusa Tenggara, Indonesia - Kamarudin (Mell Baou Publisher, 2026)
This study examines the effectiveness of Mind Mapping in improving English as a Foreign Language (EFL) students’ reading comprehension of narrative texts in a vocational school in West Nusa Tenggara, Indonesia. The study employed a quasi-experimental design involving 56 second-grade students of SMKN 7 Mataram selected through cluster random sampling. The participants were divided into an experimental group taught through Mind Mapping and a control group taught through conventional instruction. The primary data were obtained through pre-test and post-test scores, while supporting data were gathered through classroom observation, brief learning-reflection interviews, and documentation of students’ mind maps. The results showed that the experimental group improved from 60.95 to 72.38, while the control group improved from 61.42 to 66.19. The t-test value was 3.96, which was higher than the t-table value of 1.67 at the 0.05 significance level. The qualitative evidence also showed stronger student engagement, clearer identification of narrative structure, and better organization of ideas. These findings indicate that Mind Mapping is an effective visual learning strategy for strengthening EFL reading comprehension in vocational education contexts.